Kharijite - a very are Arab-Sasanian propaganda silver drahm - Warden, W. (Journal of the Oriental Numismatic Society, 1984)
The writer recently acquired a Kharijite silver drahm , which, on the basis of its date (AH 75 = AD 694), mint signature (ART - Ardeshir-Khurra, in Fars Province), marginal Pahlevi ("Bisi'llah" in second quarter) and Kufic ("La Hukma ilia lillah = No judgement save that of God" in third quarter), can be identified according to Dr. Dale L. Bishop as a propaganda issue struck by Kharijite counter Caliph Qatari ibn al-Fuja'a (see Figure 1). According to Dr. Bishop, "Another coin with the same mint, date and marginal legend has been attributed to Quatari by Walker-' on the basis of the name legend". See figure 2 for a similar drahm in the writer's collection. The name legend on both the ANS specimen (ex E. G. Weber collection) published by Dr. Bishop and the writer's, which is similar in every detail, have in place of Quatari's name and title the following Kharijite slogan: " L'(Y)T'd"twbl BR' yazd " = nest dadwar be Yazd = 'There is no Judge except God' in Pahlevi. Both coins are identical to Walker T 18 and the inscription also the same as M 53. A similar drahm in the Haddad Collection has been published by Dr. Heinz Gaube , arriving at the same conclusions as Dr. Bishop's. The great Pahlevi scholar, Salemann, seems to have been disregarded by Walker" who placed these coins in his uncertain governor's category. Perhaps this was because they were never illustrated by Mordtman and by Thomas when they published their respective coins and because their present disposition is unknown. If the coin published by Thomas (ex Bland collection) is the coin acquired by either the ANS or the writer, we have no way of knowing, but at the maximum, it would mean that there are four known Kharijite propaganda pieces of this date and mint in existence today, and also the one of AH 69, making it one of the rarest issues in the Arab-Sasanian series.
Keywords: Numismatique

Kharijites – The Kharijites and their coinage: a reply - Foss, Clive (Journal of the Oriental Numismatic Society, 2002)
Keywords: Numismatique

Kharijite – A new and unusual dirham - Foss, Clive (Journal of the Oriental Numismatic Society, 2005)
Keywords: Numismatique

Coinage of an enigmatic caliph - Kassis, Hanna E. (Al-Qantara : Revista de Estudios Arabes, 1988)
Keywords: Numismatique

Mulāḥaẓāt ḥawla Sikkat Nuqūd al-Fihriyyīn wa’l-Khawārij bi-Ifrīqiyya (128-142 H./745-759 M.) fī Ḍaw’ Majmūʿa Jadīda - ʿAṭā Allāh, Saʿīd ʿAbd al-Fattāḥ (Mishkāt: Al-Majalla al-Miṣriyya li’l-Āthār al-Islāmiyya, 2008)
As for the Ibāḍīs, a description of two coins from the period of Abū ‘l-Khaṭṭāb ʿAbd al-Aʿlà b. al-Samḥ al-Maʿāfirī, minted in 141 H., and one coin, minted in 142 H. by ʿAbd al-Raḥmān b. Rustam.
Keywords: Numismatique

Réflexions sur la révolte des berbères kharijites au Maghreb sous le gouvernement de Umar b. Hafs (151-154 / 768-771) une relecture des sources textuelles à la lumière des source numismatiques - Fenina, Abdelhamid (المجلة التونسية للعلوم الاجتماعية, 2009)
La révolte des Berbères kharijites sous le gouvernement de cUmar b. Hafs (151-154/768-771), objet de la présente étude, est relativement bien connue dans l’historiographie de l’Ifrîqiya. Toutefois, nous observons que les récits de nos chroniqueurs, dont aucun n’est contemporain des faits relatés, fourmillent d’informations tantôt confuses tantôt contradictoires. De fait, la chronologie de la révolte et certains autres faits historiques restent encore difficiles à discerner. Afin de contribuer à une meilleure connaissance de cet épisode obscur de l’histoire du Maghreb au milieu du IIe /VIIIe siècle, nous avons essayé de confronter les données recueillies dans nos sources textuelles aux témoignages numismatiques, contemporains des faits. Cette approche, nous a permis de proposer à la fois une relecture de certains faits rapportés par nos sources narratives et une chronologie de la révolte.
Keywords: Numismatique